University Professors’ Teaching Conceptions Questionnaire: An Instrument to Understand Teaching Models - Pérez-Rodríguez, Noelia; Navarro-Medina, Elisa; de-Alba-Fernández, Nicolás (Pedagogika, 2023)
This article presents the design, validation using structural equations, and results of a questionnaire about the teaching conceptions of University of Seville professors. Two differentiated samples were used: an experimental group, that included professors who were taking the General University Teaching Course and a control group of professors who were not taking the said course. The results and conclusions of the study show significant differences between the groups.